Start of enteral nutrition after an endoscopic gastrostomy, is it necessary to wait? - Otero-Regino, William (2023)
Traditionally, the initiation of enteral nutrition after a percutaneous endoscopic gastrostomy (PEG) is performed between 12 and 24 hours. Different research suggests that early initiation might be a safe option. Our aim was to determine whether starting enteral nutrition 4 hours after performing PEG is a safe practice in terms of risk of intolerance, complications, or death, compared to starting it at 12 hours. We carried out a prospective, randomized, multicenter study in third and fourth level institutions in Bogotá and Cundinamarca, between June 2020 and May 2022, 117 patients were included who were randomized into 2 groups, group A with early nutrition initiation (4 hours), and standard group B (12 hours). The most frequent mechanism of dysphagia was cerebrovascular disease (43%), followed by complications of COVID19 infection (26%). There were no statistically significant differences between the groups evaluated regarding the percentage of intolerance to nutrition, RR = 0.93 (CI 0.30-2.90), there were also no differences in terms of postoperative complications, (RR) = 0.34 (CI 0.09- 1.16), and no differences were found in mortality between the evaluated groups, (RR) = 1.12 (CI 0.59-2.15). In conclusion, early initiation of nutrition through the gastrostomy, 4 hours after performing the PEG, is a safe behavior that is not related to greater intolerance to nutrition, complications, or death, compared to later initiation.